Internet of Things (IoT) LiveLessons, 2nd Edition - Barton, Robert; Henry, Jerome (Pearson IT Certification, 2021)
Internet of Things (IoT) LiveLessons, 2nd Edition Sneak Peek The Sneak Peek program provides early access to Pearson video products and is exclusively available to Safari subscribers. Content for titles in this program is made available throughout the development cycle, so products may not be complete, edited, or finalized, including video post-production editing.
Online resource; Title from title screen (viewed September 28, 2021)
Keywords: Streaming video; Internet videos; Vidéo en continu; Vidéos sur Internet; streaming video; Electronic videos